Lalatabimba (lintel) of the doorframe probably showing a Chaturmukha Linga - Temples of India Project Team (Jio Institute, 2024)
The lalatabimba (lintel) of the doorframe probably shows a Chaturmukha Linga, flanked and worshipped by devotees and maladharas on each side. The devotees are depicted with folded hands, a gesture of paying homage and respect. Next to these devotees, maladharas are carved holding garlands for the deity. Due to withering and the presence of heavy hairlocks, the other faces of the linga, besides the frontal one, are not clearly visible in the image. Nonetheless, the withered part of the linga resembles the other faces, hinting at the possibility of it being a Chaturmukha linga.